Cellulose derivative as protection coating: Effect of nanoparticle additives on load capacity - Shi, Shih-Chen; Tsai, Xiao-Ning (Universitas Negeri Padang, 2022)
The cellulose derivative hydroxypropyl methylcellulose (HPMC) has recently been extensively studied and used in mechanical applications. However, the softness and susceptibility to deformation of HPMC limited its further applications. In this study, metal nanoparticles (nano-aluminum and nano-copper) and nano-metal oxide particles (nano-alumina and nano-copper oxide) were used as additives to HPMC to form a composite film with improved mechanical properties, particularly load capacity. The addition of high levels of additives provided a higher load capacity. Among the nano-additives used in the study, Cu (2 wt.%) provided the composite with the highest load capacity, improving the load capacity of pure HPMC by 250%. The surface treatment of strengthening additives is an important step. Adding specific high-strength and high-modulus metal and metal oxide additives to the soft HPMC matrix can effectively improve the load-bearing capacity of the composite material. This study proposes a simple evaluation method for the load-bearing capability of the coating as well.